Targeting Thyroid Hormone Receptor Interacting Protein (TRIP13) for Cancer Therapy: A Promising Approach - Surya P. Singh; Krishnendu Goswami; Gopal Pathuri; Chinthalapally V. Rao; Venkateshwar Madka (DNA)
TRIP13 is a member of the large AAA+ ATPase protein superfamily that plays a crucial role in the precise segregation of chromosomes during mitosis. The abnormal function of TRIP13 has diverse functions, including mitotic processes, DNA repair pathways, and spindle assembly checkpoints, which may contribute to chromosomal instability (CIN). Emerging evidence suggests that the overexpression of TRIP13, observed in many cancers, plays a significant role in drug resistance, autophagy, and immune invasion. Recently, significant advances have been made in identifying TRIP13-associated signaling pathways that have been implicated in cancer progression. Several small molecules that specifically inhibit TRIP13 function and reduce cancer cell growth have been developed. Combination treatments, including TRIP13 inhibitors and other anticancer drugs, have shown promising results. While these findings are promising, TRIP13 inhibitors are awaiting clinical trials. This review discusses recent progress in understanding the oncogenic function of TRIP13 and its possible therapeutic targets, which could be exploited as an attractive option for cancer management.